EVALUATION OF THE HEMOSTATIC EFFECTS OF ALAI MUMIYO EXTRACT (7.5 MG/KG) ON BLOOD COAGULATION PARAMETERS IN DOGS - Kurbanova Diloramxon Ibragimdjan qizi (Western European Studies, 2025)
The influence of Alai Mumiyo extract at a dose of 7.5 mg/kg on blood coagulation in dogs was investigated. Ten clinically healthy animals received the extract orally, and coagulation indices were evaluated at baseline as well as 30 and 60 minutes after administration. The extract produced a significant prolongation of blood clotting, plasma recalcification, and thrombin times, along with an increase in plasma tolerance to heparin and stimulation of fibrinolytic activity (p < 0.05). Fibrinogen concentration showed a slight decrease, whereas the activities of coagulation factors and total protein levels remained stable. These findings suggest that Alai Mumiyo possesses notable anticoagulant and fibrinolytic properties, supporting its potential role as a natural modulator of hemostasis
Keywords: Alai Mumiyo extract; blood coagulation; thrombin time